ANALISIS PENGARUH PERTUMBUHAN EKONOMI, UPAH, DANPERTUMBUHAN PENDUDUK, TERHADAP KESEMPATAN KERJA DIPROVINSI RIAU PERIODE 2011-2020 - Pasaribu, Riski Leonardo; Dahlan Tampubolon; Wahyu Hamidi (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2023)
The purpose of this study is to determine the effect of simultaneouslyeconomic growth, wages, and population growth on employment opportunities in Riau Province. The populationthat will be taken in this study is data collected and taken through BPS data of Riau Province. In this case, the sample is taken as a sample, namely the last 10 years from 2011 - 2020. The method used in sampling this research is Purposive Sampling, namely the technique of determining thesample. with certain considerations or criteria.From the results of R Square (coefficient of determination) that is equal to53% while the rest is influenced by other variables outside the variables in thisstudy. Simultaneously, it is known that Fcount < Ftable is 1.792 < 4.76 and thesignificant level is 0.249> 0.05. This indicates that simultaneously the variables ofeconomic growth, wages, and population growth do not have a significant effecton employment opportunities in Riau province during the 2011-2020 period. Theresults of the correlation test show that the Wage and Employment Opportunityvariable has a negative relationship value with a correlation value of -0.523because it is in the coefficient interval of 0.00-0.199. Weaknesses in this study are limitations in the variables studied, which are partly explained by variables that are not included in the study.